Five decades of sarcoma care at Memorial Sloan Kettering Cancer Center. Issue 5 (10th September 2022) - Brennan, Murray F.; Singer, Samuel
Abstract: Early studies of the management of soft tissue sarcoma at Memorial Sloan Kettering Cancer Center were influenced by development of robust prospective long‐term databases. Increasing capacity for molecular diagnostics has identified a myriad of subtypes with definable natural history. Accurate identification of tissue‐specific risk of recurrence and disease‐specific survival have increasingly allowed selective use of surgery, radiation therapy, and target‐specific cytotoxic and immune therapies.